"Here, There, in between, beyond...": Identity Negotiation and Sense of Belonging among Southern Europeans in the UK and Germany - Quassoli, Fabio (Social Inclusion, 2019)
Whilst most of the research on intra-EU mobility has mainly focused on the reasons behind young Southern Europeans leaving their home countries, and secondly on their experiences within the new context, little is known about their sense of belonging and identities. This article aims to fill this gap by exploring Italian and Spanish migrants’ social identity repositioning and the cultural change characterising their existential trajectories. Drawing on 69 semi-structured interviews with Italians and Spaniards living in London and Berlin, this article shows that the sense of belonging to one or more political communities and boundary work are related to individual experiences and can change due to structural eventualities such as the Brexit referendum. While identification with the host society is rare, attachment to the home country is quite common as a result of people’s everyday experiences. Cultural changes and European/cosmopolitan identification are linked to exposure to new environments and interaction with new cultures, mostly concerning those with previous mobility experience, as well as to a sentiment of non-acceptance in the UK. However, such categories are not rigid, but many times self-identification and attachments are rather blurred also due to the uncertainty around the duration of the mobility project. This makes individual factors (gender, age, family status, employment, education) that are often considered as determinants of identification patterns all but relevant.